Shakespearean perspectives - doi: 10.4025/actascilangcult.v33i1.10109 - Teles, Adriana da Costa; Harris, Peter James (Acta Scientiarum. Language and Culture, 2011)
LEÃO, Liana de Camargo; SANTOS, Marlene Soares. Shakespeare, sua época e sua obra. Curitiba: Beatrice, 2008. 360 p. ISBN: 978856078000-6.